2013
DOI: 10.2320/jinstmet.77.7
|View full text |Cite
|
Sign up to set email alerts
|

Metal Silicide on the Steel Substrate Formed by Atmospheric Controlled IH-FPP (AIH-FPP) and Its Effect on Corrosion Resistance Improvement

Abstract: Metal silicides are potential materials because of their excellent properties such as corrosion resistance, oxidation resistance and wear resistance. In this study, the authors propose a new surface treatment process to form metal silicides on metallic materials by using an atmospheric controlled IH FPP. Atmospheric controlled IH FPP in which Si particles are bombarded to the substrate with an elevated temperature of 1173 K can form the iron silicide. Elevated temperature of the substrate enhances transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Ti-Al 金属間化合物は,軽量で耐食性や耐摩耗性に加えて 耐熱性にも優れるため,高温構造材料としての利用が期待さ れている.実際,自動車のターボチャージャーなどの素材と して最近利用され始めている.しかし,靱性や延性に乏しく 脆いという欠点を有しているため,バルク材を部品形状に機 械加工して利用することは困難である.そこでこの金属間化 合物を,靱性の高い基材へコーティングすることで,その優 れた特性を最大限に活かす試み 1,2) が検討されている. 本研究では,この金属間化合物を鋼の表面に被覆する手法 として,著者らが開発した AIH-FPP (Atmospheric controlled Induction Heating Fine Particle Peening) 処理 [3][4][5][6][7][8][9][10][11][12][13][14] に着目した.…”
unclassified
“…Ti-Al 金属間化合物は,軽量で耐食性や耐摩耗性に加えて 耐熱性にも優れるため,高温構造材料としての利用が期待さ れている.実際,自動車のターボチャージャーなどの素材と して最近利用され始めている.しかし,靱性や延性に乏しく 脆いという欠点を有しているため,バルク材を部品形状に機 械加工して利用することは困難である.そこでこの金属間化 合物を,靱性の高い基材へコーティングすることで,その優 れた特性を最大限に活かす試み 1,2) が検討されている. 本研究では,この金属間化合物を鋼の表面に被覆する手法 として,著者らが開発した AIH-FPP (Atmospheric controlled Induction Heating Fine Particle Peening) 処理 [3][4][5][6][7][8][9][10][11][12][13][14] に着目した.…”
unclassified
“…14) On the other hand, the authors have demonstrated atmospheric controlled induction heating fine particle peening (AIH-FPP) 5) treatment as an alternative technique for the same purpose. 6,7) Our work has recently shown that intermetallic compound layers can be produced on the surface of carbon steel by AIH-FPP treatment via a combustion synthesis reaction 8,9) that occurs on the surface of the treated material. 10,11) We have also proposed that mechanically-milled shot particles containing different elements could be used to create homogeneous intermetallic compound layers.…”
Section: Introductionmentioning
confidence: 99%
“…A treated specimen surface can be simultaneously modified by plastic deformation and quenching. Recently, there have been reports concerning the creation of a modified layer by using this treatment system [2][3][4]. IH-FPP treatment of SCM435 steel is highly effective in improving the fatigue strength of steel [5].…”
Section: Introductionmentioning
confidence: 99%